CAREER DECISION MAKING PROCESS OF THE 8TH GRADERS WITHIN THE REFORM PROCESSES IN LATVIA - Ilisko, Dzintra; Šapale, Sandra; Šimáně, Michal (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The present study investigates the career choice of 8th graders in the context of reform processes in Latvia and changing demands of the job market. Career planning in this article is seen as a spiralling and dialectic process that is influenced by multiple factors, the process that involves planning, generating options, evaluation of options and making decisions. Reform processes in Latvia requires career counsellors to help young people to maintain an attitude of acceptance while choosing a career path, and in addition to develop meaningful and professional life changing discussion on available career options in order to become significant adviser while guiding pupils on adapting to changing requirements of a job market. The aim of the study is to explore the main influences determining the career choice of the 8th grade pupils as well as to explore the sources of information that determine them on making such decisions. Research methodology: For the purpose of this study the authors chose a pilot questionnaire in order to explore the career path of the 8th graders. The study draws on tendencies of youngsters’ choice of a career obtained in Latvia and Czech Republic. Research findings: Considering the changing demands of a job market, the teachers need to consider an adaptive career managing processes for the youngsters by taking into account a dialectic interplay of multiple influences on pupils’ career choice and to foster a more sustainable career path in helping pupils to gain career maturity in decision making and developing competencies needed for the future.